A Study on Generation’s Perceptions About Investing in Mutual Fund and Hedge Funds in Ahmedabad City - Paikaray, Katyayani; Acharya, Jinal; Vidani, Dr Jignesh (International Journal of Economic, Finance and Business Statistics, 2024)
This research analysis takes into consideration perceptions of investments in mutual funds and hedge funds by Generation Z within Ahmedabad, factoring the influence of age on awareness, preferences, and concerns over those investment vehicles. A chi-square analysis suggests that there are significant relationships between age and a number of dimensions of investment understanding. For instance, the older members of Generation Z show a better understanding of hedge funds, whereas perceptions of mutual funds as risk-free investments are stronger among younger individuals. The study finds a gap in knowledge regarding differences between mutual fund and hedge fund investments and various other factors impacting the investment decisions that include professional management and risk perception. Thus, findings show that personalized financial education schemes through training programmes help remove misconceptions and build improved financial literacy among young investors. In this regard, stakeholders can help this demographic develop an informed investment practice by tapping onto digital platforms and connecting with them via interactive programs. Thus, the value of this study lies in the understanding of Generation Z's unique financial perspectives in the promotion of responsible investing practice and long-term financial outcomes.